The Relationship Between Emotional Intelligence and Academic Achievement of Tenth Grade Students at Vocational School SMK Immanuel Medan - Karuna Wirajaya Wangi; Lilis Handayani Napitupulu; Enjelika Silaen (ELT (English Language Teaching Prima Journal), 2024)
This study is conducted to find the relationship between emotional intelignce intelligence and Academic achievement of tenth grade, which is conducted at vocational school smk immanuel medan Quantitative relationship investigation was used in this investigation. Correlational investigations investigate employment insights to decide whether there is a relationship and the degree of relationship between two variables. The essence of this investigation is to determine and analyze the relationship between emotional intelligence and academic achievement of tenth grade students at vocational school SMK Immanuel Medan. Pre test and post test are used to measure whether there is a significance of using methods or without using method. The results of the investigation the relationship between emotional intelligence and academic achievement of tenth grade students at vocational school SMK Immanuel Medan show that there is a relationship, shown and included, with the high value of the results of the investigation of the information obtained. The relationship between emotional intelligence and academic achievement of tenth grade students at vocational school SMK Immanuel Medan. The higher the emotional intelligence possessed by students, the higher the learning achievements they can obtain.